Упростить выражение: [latex]1) \frac{a+b}{\sqrt{ab}-b}- \frac{2\sqrt{a}}{\sqrt{a}-\sqrt{b}} \\ \\ 2) ( \frac{2\sqrt{x}}{2\sqrt{x}+\sqrt{y}}-\frac{4x}{4x+4\sqrt{xy}+y}):(\frac{2\sqrt{x}}{4x-y}+\frac{1}{ \sqrt{y}-2\sqrt{x}}) [...

Упростить выражение: [latex]1) \frac{a+b}{\sqrt{ab}-b}- \frac{2\sqrt{a}}{\sqrt{a}-\sqrt{b}} \\ \\ 2) ( \frac{2\sqrt{x}}{2\sqrt{x}+\sqrt{y}}-\frac{4x}{4x+4\sqrt{xy}+y}):(\frac{2\sqrt{x}}{4x-y}+\frac{1}{ \sqrt{y}-2\sqrt{x}}) [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1 (a+b)/√b(√a-√b) -2√a/(√a-√b)=(a+b-2√ab)/√b(√a-√b)=(√a-√b)²/√b(√a-√b)= =(√a-√b)/√b 2 1)2√x/(2√x+√y)-4x/(2√x+√y)²=(4x+2√xy-4x)/(2√x+√y)²=2√xy/(2√x+√y)² 2)2√x/(2√x-√y)(2√x+√y)-1/(2√x-√y)=(2√x-2√x-√y)/(2√x-√y)(2√x+√y)= =-√y/(2√x-√y)(2√x+√y)=√y/(√y-2√x)(2√x+√y) 3)2√xy/(2√x+√y)²:√y/(√y-2√x)(2√x+√y)=2√xy/(2√x+√y)²*(√y-2√x)(2√√x+√y)/√y= =2√x(√y-2√x)/(2√x+√y)
Гость
1) = (a+b)/√b(√a -√b)  -2√a/(√a -√b) =(a+b-2√a√b)/√b(√a -√b) = (√a -√b)²/√b(√a -√b)=(√a -√b)/√b.  || (√(a/b) -1 || --- 2) (2√x/(2√x +√y) - 4x/(4x+4√(xy) +y)) : (2√x /(4x -y) +1/(√y -2√x) ) = ((2√x*(2√x +√y) - 4x)/(2√x +√y)²) : (2√x /(2√x -√y)(2√x+√y) -1/(2√x -√y) ) = (2√(xy)/(2√x +√y)²) : (2√x -2√x-√y) /(2√x -√y)(2√x+√y) )= (2√(xy)/(2√x +√y)²) * ((2√x -√y)(2√x+√y)/(-√y) ) = 2√(x)*(√y -2√x)/(2√x +√y).
Не нашли ответ?
Ответить на вопрос
Похожие вопросы